Phytoplankton pigment and phytoplankton group chlorophyll-a concentrations during POLARSTERN cruise PS126 from North Sea to Fram Strait in May to June 2021 from HPLC analysis of water samples - Bracher, Astrid; Xi, Hongyan; Hohe, Christian; Wiegmann, Sonja; Peeken, Ilka (PANGAEA, 2025)
Phytoplankton pigments were determined in the water surface (from 0 to 11 m depth) of a transect from the North Sea to Fram Strait and back during RV Polarstern expedition PS126 from 24 May to 25 June 2021. Water samples were collected from CTD Niskin bottles at five to six different depths from the upper 100 m at CTD stations and from underway sampling. Between 0.4 to 3.5 L of each seawater sample was filtered through Whatman GF/F filters. The sample filters were then shock‐frozen in liquid N2 and kept at−80 °C until analysis. High Pressure Liquid Chromatography (HPLC) was performed to quantify various phytoplankton pigments (see Table 1 in Taylor et al. 2011) following the method of Barlow et al. (1997) that was adjusted to our temperature‐controlled instruments as detailed in Alvarez et al. (2022).
Keywords: HPLC analysis; North Sea; phytoplankton groups; phytoplankton pigments